2017
DOI: 10.5194/hess-2017-511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoupling of dissolved organic matter patterns between stream and riparian groundwater in a headwater forested catchment

Abstract: Abstract. Streams are important sources of carbon to the atmosphere, though whether they merely outgas terrestrially derived 10 carbon dioxide or mineralize terrestrial inputs of dissolved organic matter (DOM) is still a big challenge in ecology. The objective of this study was to investigate the influence of riparian groundwater (GW) and in-stream processes on the temporal pattern of stream DOM concentrations and quality in a forested headwater stream, and whether this influence differed between the leaf litt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The relationships between DOC/DON and landscape conditions were also explored to provide information on possible sources of DON (Figure 7). If DOC and DON were generated from the same organic matter and degrading at similar rates, we would expect similar patterns in ratios across different landscape conditions (Bernal et al, 2017). Different trends between DON and DOC/DON across landscape conditions would suggest different sources and/or degradation rates or labilities between DOC and DON.…”
Section: Doc/don Ratio Under Different Landscape Conditionsmentioning
confidence: 97%
“…The relationships between DOC/DON and landscape conditions were also explored to provide information on possible sources of DON (Figure 7). If DOC and DON were generated from the same organic matter and degrading at similar rates, we would expect similar patterns in ratios across different landscape conditions (Bernal et al, 2017). Different trends between DON and DOC/DON across landscape conditions would suggest different sources and/or degradation rates or labilities between DOC and DON.…”
Section: Doc/don Ratio Under Different Landscape Conditionsmentioning
confidence: 97%
“…The upstream site drains a steep area where soils are well-drained, and no riparian forest can develop. As geomorphology becomes more favourable for the development of wetter soils in the near-stream zone, riparian forests can establish and support relatively larger mobilization of DOC from the riparian zone to the stream (Inamdar and Mitchell, 2006;Bernal et al, 2018). However, DOC concentrations decreased ca.…”
Section: Hydroclimatic Analysis Of Storm Eventsmentioning
confidence: 99%
“…In this stream, NO − 3 is the major source of N for stream heterotrophic microorganisms, accounting for more than 90 % of the dissolved inorganic N (Bernal et al, 2015) and more than 80 % of the total dissolved N (unpublished data). Yet, ambient DOC and NO − 3 concentrations are relatively low compared to forest headwater streams located elsewhere (Hartmann et al, 2014;Bernal et al, 2015Bernal et al, , 2018, and we expected hydrological conditions and the presence of riparian forests to have a significant influence on the supply of these limited solutes for stream heterotrophic microorganisms. In order to fulfil our aim, we analysed DOC and NO − 3 concentrations and DOC : NO − 3 molar ratios under base flow and storm flow conditions at three stream locations along a longitudinal gradient of increasing riparian forest coverage.…”
Section: Introductionmentioning
confidence: 95%
“…Running waters play a critical role in the global carbon (C) cycle because they transport dissolved organic carbon (DOC) from 35 lands to oceans (Cole et al, 2007). Accounting for stream DOC fluxes within stream networks can be valuable for understanding net in-stream C retention (Alexander et al, 2007;Bernal et al, 2018) and catchment-integrated evasion of C (Wallin et al, 2013), as well as for assessing and managing the brownification of large water bodies (Kritzberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The 40 organization of flow paths to riparian zones (RZ) (Jencso et al, 2010;McGlynn and McDonnell, 2003;Ploum et al, 2020), riparian wetness regimes (Vidon, 2017), and local differences in soil organic carbon stocks (Grabs et al, 2012) are major controls of the spatiotemporal variability of terrestrial DOC fluxes to streams. Further, recent studies have shown that headwaters can have a reactive role as well, which can reduce downstream supply of DOC (Bernal et al, 2018;Hotchkiss et al, 2015). Mineralization by biota is a major removal mechanism of terrestrial DOC, in addition to abiotic processes such as 45 adsorption, flocculation, and photooxidation (Mineau et al, 2016).…”
Section: Introductionmentioning
confidence: 99%